THE INFLUENCE OF ENVIRONMENT TOWARDS JEAN LA’BARGE IN LOUIS L’AMOUR’S SITKA - Laili Nurwakhidah; Mateus Rudi Supsiadji (Anaphora : Journal of Language, Literary, and Cultural Studies, 2020)
This study is about the influence of the environments toward Jean LaBarge's in Sitka. The novel analyzed with qualitative descriptive research method and sociological approach. The analysis shows that character of Jean LaBarge gets influences from nature and other characters in his development. Jean is influenced by the great swamp and Alaska which makes him brave, independent, and ambitious. In addition, there is some social environment influencing him. His father, Captain Hutchins, Peter Hovey, Rob J. Walker, and Princess Helena Gagarin. Jean's characteristics were formed by both nature and social environment.